Stress, Anxiety, and School Burnout Post COVID-19: A Study of French Adolescents - Simoës-Perlant, Aurélie; Barreau, Marion; Vezilier, Caroline (Mind, Brain, and Education, 2023)
This study examined the symptoms of exhaustion, school stress and anxious school refusal from a comparative developmental perspective in French adolescents enrolled in public and private general, technological and vocational schools. It is particularly important to consider academic stress levels, anxiety and school burnout in middle and high school students as they are linked to many mental health problems, such as depression or suicidal thoughts. In this study, four hundred and ninety-three adolescents completed an online questionnaire consisting of the School Burnout Inventory, the Echelle Toulousaine de Stress Scolaire perçu and the School refusal evaluation was developed. The results show a very high percentage of suffering among teenagers. The young people most affected are high school students and more particularly students in 10th and 12th grade, with nearly three-quarters of them suffering from school burnout and/or high school stress, without any distinction between the sexes or the type of schooling.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/mbe.12346